2014
DOI: 10.1371/journal.pone.0107677
|View full text |Cite
|
Sign up to set email alerts
|

MET Gene Copy Number Predicts Worse Overall Survival in Patients with Non-Small Cell Lung Cancer (NSCLC); A Systematic Review and Meta-Analysis

Abstract: ObjectivesMET is a receptor present in the membrane of NSCLC cells and is known to promote cell proliferation, survival and migration. MET gene copy number is a common genetic alteration and inhibition o MET emerges as a promising targeted therapy in NSCLC. Here we aim to combine in a meta-analysis, data on the effect of high MET gene copy number on the overall survival of patients with resected NSCLC.MethodsTwo independent investigators applied parallel search strategies with the terms “MET AND lung cancer”, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 32 publications
(27 reference statements)
1
29
2
Order By: Relevance
“…The prevalence of MET amplification is ~5% in untreated patients and 20% in those with acquired resistance to EGFR-TKIs (2131). MET positivity via IHC and an increased MET gene copy number are both significantly associated with poor overall survival (2124,32). Although some preclinical studies, phase I/II trials, and subgroup analyses of phase III trials of small molecules targeting MET (used either singly or in combination) for MET -amplified NSCLC have yielded favorable results, the efficacy of such agents has not yet been confirmed in large clinical trials (10,3335).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of MET amplification is ~5% in untreated patients and 20% in those with acquired resistance to EGFR-TKIs (2131). MET positivity via IHC and an increased MET gene copy number are both significantly associated with poor overall survival (2124,32). Although some preclinical studies, phase I/II trials, and subgroup analyses of phase III trials of small molecules targeting MET (used either singly or in combination) for MET -amplified NSCLC have yielded favorable results, the efficacy of such agents has not yet been confirmed in large clinical trials (10,3335).…”
Section: Discussionmentioning
confidence: 99%
“…6063 This frequency depends on the antibody, assay, and the positivity cut-point. While MET protein expression has been associated with poor prognostic outcomes in lung cancer, 60, 64 it has thus far served as a poor predictive biomarker of response to targeted therapy.…”
Section: Met As a Co-driver In Nsclcmentioning
confidence: 99%
“…Amplification of MET (and overexpression of the protein) is also a common event in brain metastases of NSCLC (59). Furthermore, fluorescence in situ hybridization (FISH)-positive MET status predicts worse survival in patients with advanced NSCLC (56,60). An analysis of OS based on MET FISH status-derived GCN revealed that increased GCN is an independent negative prognostic factor in surgically resected NSCLC, with OS of 25.8 months for patients with MET !5 copies/cell compared with 47.5 months for patients with MET <5 copies/cell (P ¼ 0.0045; ref.…”
Section: Met Amplificationmentioning
confidence: 99%